2019
DOI: 10.1038/s41416-019-0683-3
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of vismodegib, a hedgehog inhibitor, combined with gemcitabine and nab-paclitaxel in patients with untreated metastatic pancreatic adenocarcinoma

Abstract: BACKGROUND: The Hedgehog (Hh) signalling pathway is overexpressed in pancreatic ductal adenocarcinoma (PDA). Preclinical studies have shown that Hh inhibitors reduce pancreatic cancer stem cells (pCSC), stroma and Hh signalling. METHODS: Patients with previously untreated metastatic PDA were treated with gemcitabine and nab-paclitaxel. Vismodegib was added starting on the second cycle. The primary endpoint was progression-free survival (PFS) as compared with historical controls. Tumour biopsies to assess pCSC,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
73
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(77 citation statements)
references
References 38 publications
4
73
0
Order By: Relevance
“…It can also suppress pancreatic CSC proliferation and survival by inhibiting Hh signaling pathways [90]. In a phase II trial, vismodegib combined with gemcitabine and nab-paclitaxel was used against untreated metastatic pancreatic cancer [91]. In another phase Ib/II trial, vismodegib plus gemcitabine was used to treat metastatic pancreatic cancer [92].…”
Section: Hh Signaling Pathway Inhibitorsmentioning
confidence: 99%
“…It can also suppress pancreatic CSC proliferation and survival by inhibiting Hh signaling pathways [90]. In a phase II trial, vismodegib combined with gemcitabine and nab-paclitaxel was used against untreated metastatic pancreatic cancer [91]. In another phase Ib/II trial, vismodegib plus gemcitabine was used to treat metastatic pancreatic cancer [92].…”
Section: Hh Signaling Pathway Inhibitorsmentioning
confidence: 99%
“…In a phase II trial, vismodegib has suggested efficacy in some pediatric patients with medulloblastoma [193]. Conversely, no clinical benefit was observed in phase II trials in other tumors including: PDAC [194,195], colorectal cancer [196], gastric and gastroesophageal junction carcinoma [197], small cell lung cancer [198], and ovarian cancer [199]. On the contrary, sonidegib showed possible efficacy in triple negative breast cancer patients in a phase I trial [200].…”
Section: Ccn2mentioning
confidence: 99%
“…Finally, the hedgehog signaling pathway involving the Sonic Hedgehog (SHH) proteins promoted desmoplasia [ 107 ] and stimulated stellate cell differentiation and myofibroblast activation in pancreatic cancer. SHH inhibition showed promising results in mouse models but did not improve OS in clinical trials [ 150 , 151 ]. As hedgehog-signaling CAFs are heterogenous and encompass several subsets [ 6 ], one hypothesis for this failure is the absence of targeting of protumoral CAF subsets.…”
Section: Therapeutic Implicationsmentioning
confidence: 99%